How Students Choose Their Majors in Information Technology (The International Journal of Engineering & Information Technology (IJEIT), 2024)
this research summarizes the results of a study conducted at the Faculty of Information Technology at Misurata University. The study was a survey intended to clarify the motivation behind students’ choices of their majors at the faculty. The aim was to understand the reasons behind the overwhelming demand on some departments and the students’ reluctance to join some other departments. The study showed that not only does the numbers of current students differ widely among the different departments, but also the number of expected students. The study also showed that students are only affected by their colleagues with regard to choosing a major